Kepatuhan Kelompok Sasaran sebagai Penentu Keberhasilan Implementasi Kebijakan: Studi Kasus Implementasi PERDA Kota Bandung Nomor 4 Tahun 2011 tentang Penataan dan Pembinaan Pedagang Kaki Lima - Rachmawati, Tutik (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2015)
The management and organisation of street vendors in Bandung City Government is regulated through the Local Government Act of Bandung City Number 4 Year 2011. The implementation of this local government act, however, is unsuccesful due to internal factor from the street vendors themselves as well as external factors such as the buyers.Â Both street vendors and the buyers showed non-compliance behaviors toward the regulation implementation. Using qualitative research design, this research showed evidence that factors such as (1) lack of incentives and heavy sanctions; (2) problem of monitoring; (3) lack of resources; (4) lack of autonomy; (5) lack of information and (6) belief and values. The results suggest a design for reshape and redesign the public policy in the management and organisation of street vendors. It highlights six aspects need to be done; (1) the involvement of â€˜street level bureaucratsâ€™; (2) consistent law enforcement; (3) incentive for compliance behaviour; (4) regards the cost and risk bear by the street vendors in the evaluation and re-designing of the policy; (5) the capacity development of the street vendors association and (6) developing a model for an effective information dissemination